2014
DOI: 10.1158/1535-7163.mct-14-0087
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-Mediated Integrin Deregulation as a Novel Mode of Action for the Anticancer Gallium Compound KP46

Abstract: On the basis of enhanced tumor accumulation and bone affinity, gallium compounds are under development as anticancer and antimetastatic agents. In this study, we analyzed molecular targets of one of the lead anticancer gallium complexes [KP46, Tris(8-quinolinolato)gallium(III)] focusing on colon and lung cancer. Within a few hours, KP46 treatment at low micromolar concentrations induced cell body contraction and loss of adhesion followed by prompt cell decomposition. This rapid KP46-induced cell death lacked c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…Cells grown in spheroids are known to produce increased amounts of adhesion molecules [49], which in general mediate invasiveness. KP46 has been reported recently to down-regulate focal adhesion proteins, in particular integrin-b1, causing deregulation of cell-matrix adhesion [50]. In good agreement with these findings, we showed that KP46 inhibits contraction of collagen I gels by fibroblasts and fibroblast invasion into collagen I, corroborating the impact on stroma interactions caused by treatment with this compound.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cells grown in spheroids are known to produce increased amounts of adhesion molecules [49], which in general mediate invasiveness. KP46 has been reported recently to down-regulate focal adhesion proteins, in particular integrin-b1, causing deregulation of cell-matrix adhesion [50]. In good agreement with these findings, we showed that KP46 inhibits contraction of collagen I gels by fibroblasts and fibroblast invasion into collagen I, corroborating the impact on stroma interactions caused by treatment with this compound.…”
Section: Discussionsupporting
confidence: 91%
“…In good agreement with these findings, we showed that KP46 inhibits contraction of collagen I gels by fibroblasts and fibroblast invasion into collagen I, corroborating the impact on stroma interactions caused by treatment with this compound. We showed further that KP46 down-regulates α-SMA in monolayer culture of fibroblasts in a dosedependent manner, which can be an additional reason not only for the anti-invasive activity of the compound, but also for cell morphology changes and cell detachment observed in fibroblasts (see Electronic supplementary material) and cancer cell lines [50]. Data obtained from HCT116/fibroblast co-culture in a 3D matrix, however, showed that KP46 selectively targets cancer cells but has no discernible impact on fibroblast viability.…”
Section: Discussionmentioning
confidence: 67%
“…The cytotoxicity mechanism involves p53 activation mediated by Ca 2+ -signalling and ROS production (Gogna et al, 2012;Madan et al, 2013). Recently, new insights onto the mechanism of action have been highlighted (Jungwirth et al, 2014). KP46 has been tested in various phase II clinical trials and no dose-limiting toxicity was found.…”
Section: Galliummentioning
confidence: 99%
“…For histological evaluations, 3 μm formalin-fixed and paraffin-embedded tumor sections were deparaffinised and rehydrated. Sections were stained with hematoxylin and eosin (H&E), Ki-67 (clone MiB-1; DAKO, Glostrup, Denmark) 1:100, and integrin β1 (CD29, #610467; BD Bioscience, NJ, USA) 1:400 as described previously [80]. …”
Section: Methodsmentioning
confidence: 99%